Influence of Logistics Optimization on Performance of Freight Forwarding Companies in Kenya - Muoki, Raphael Kiluu; Moronge, Makori (International Journal of Supply Chain and Logistics, 2021)
Purpose: The purpose of the study is to investigate the influence of logistics optimization on performance of freight forwarding companies in Kenya. Methodology: Descriptive research design was adopted. The study preferred this method because it allows an in-depth study of the subject. Data was collected from deputy heads and heads of procurement in 45 freight forwarding companies in Kenya, who are registered members of KIFWA according to its 2019 directory. Questionnaires were used to collect data. The questionnaires were tested for validity and reliability using 10% of the total sample respondents. Data was analyzed through descriptive statistical methods such as means, standard deviation, frequencies and percentage. Inferential analyses were used in relation to correlation analysis and regression analysis to test the relationship between the four explanatory variables and the explained variable. Multiple regression models were used to show the relationship between the predicted variable and the predictor variables. Results and conclusion: The independent variables reported R value of 0.846 indicating that there is perfect relationship between dependent variable and independent variables. R square value of 0.716 which means that 71.6% of the corresponding variation in performance of the freight forwarding companies can be explained or predicted by (logistics information system, freight management, distributor base rationalization and transport planning) which indicated that the model fitted the study data. The findings of the study indicated that logistics information system, freight management, distributor base rationalization and transport planning have a positive relationship with performance of freight forwarding companies in Kenya. Unique contribution to theory, policy and practice: the study recommended that freight forwarding companies should embrace logistics optimization so as to improve performance and further researches should to be carried out in other institutions to find out if the same results can be obtained.